Dehydrogenation of saturated CC and BN bonds at cationic N-heterocyclic carbene stabilized M(III) centers (M = Rh, Ir). - Tang, C; Thompson, A; Aldridge, S (2010)
Chloride abstraction from the group 9 metal bis(N-heterocyclic carbene) complexes M(NHC)(2)(H)(2)Cl [M = Rh, Ir; NHC = IPr = N,N'-bis(2,6-diisopropylphenyl)imidazol-2-ylidene or IMes = N,N'-bis(2,4,6-trimethylphenyl)imidazol-2-ylidene] leads to the formation of highly reactive cationic species capable of the dehydrogenation of saturated CC and BN linkages. Thus, the reaction of Ir(IPr)(2)(H)(2)Cl (1) with Na[BAr(f)(4)] in fluorobenzene generates [Ir(IPr)(2)(H)(2)](+)[BAr(f)(4)](-) (4) in which the iridium center is stabilized by a pair of agostic interactions utilizing the methyl groups of the isopropyl substituents. After a prolonged reaction period C-H activation occurs, ultimately leading to the dehydrogenation of one of the carbene (i)Pr substituents and the formation of [Ir(IPr)(IPr'')(H)(2)](+)[BAr(f)(4)](-) (5), featuring the mixed NHC/alkene donor IPr'' ligand. By contrast, the related IMes complexes M(IMes)(2)(H)(2)Cl (M = Rh, Ir), which feature carbene substituents lacking beta-hydrogens, react with Na[BAr(f)(4)] in fluorobenzene to give rare examples of NaCl inclusion compounds, viz., [M(IMes)(2)(H)(2)Cl(Na)](+)[BAr(f)(4)](-) (M = Rh, 6; M = Ir, 7). Intercalation of the sodium cation between the mesityl aromatic rings of the two NHC donors has been demonstrated by crystallographic studies of 7. Synthetically, 6 and 7 represent convenient yet highly reactive sources of the putative 14-electron [M(NHC)(2)(H)(2)](+) cations, readily eliminating NaCl in the presence of potential donors. Thus 7 can be employed in the synthesis of the dinitrogen complexes [Ir(IMes)(2)(N(2))(2)](+)[BAr(f)(4)](-) (8a) and [Ir(IMes)(2)(N(2))THF](+)[BAr(f)(4)](-) (8b) (albeit with additional loss of H(2)) by stirring in toluene under a dinitrogen atmosphere and recrystallization from the appropriate solvent system. The interactions of 6 and 7 with primary, secondary, and tertiary amineboranes have also been investigated. Although reaction with the latter class of reagent simply leads to coordination of the amineborane at the metal center via two M-H-B bridges {and formation, for example, of the 18-electron species [M(IMes)(2)(H)(2)(mu-H)(2)B(H).NMe(3)](+)[BAr(f)(4)](-) (M = Rh, 9; M = Ir, 10)}, the corresponding reactions with systems containing N-H bonds proceed via dehydrogenation of the BN moiety to give complexes containing unsaturated aminoborane ligands. Thus, for example, 6 catalyzes the dehydrogenation of R(2)NH x BH(3) (R = (i)Pr, Cy) in fluorobenzene solution (100% conversion over 6 h at 2 mol % loading) to give R(2)NBH(2); the organometallic complex isolated at the end of the catalytic run in each case is shown to be [Rh(IMes)(2)(H)(2)(mu-H)(2)BNR(2)](+)[BAr(f)(4)](-) (R = (i)Pr, 11; R = Cy, 12). In contrast to isoelectronic alkene donors, the aminoborane ligand in these complexes (and in the corresponding iridium compounds 13 and 14) can be shown by crystallographic methods to bind in end-on fashion via a bis(sigma-borane) motif. Similar dehydrogenation chemistry is applicable to the primary amineborane (t)BuNH(2) x BH(3), although in this case the rate of rhodium-catalyzed dehydrogenation is markedly slower. This enables the amineborane complex [Rh(IMes)(2)(H)(2)(mu-H)(2)B(H) x NH(2)(t)Bu](+)[BAr(f)(4)](-) (15) to be isolated at short reaction times (ca. 6 h) and the corresponding (dehydrogenated) aminoborane system [Rh(IMes)(2)(H)(2)(mu-H)(2)BNH(t)Bu](+)[BAr(f)(4)](-) (16) to be isolated after an extended period (ca. 48 h). As far as further reactivity is concerned, aminoborane systems such as 14 show themselves to be amenable to further dehydrogenation chemistry in the presence of tert-butylethylene leading ultimately to the dehydrogenation of the boron-containing ligand and to the formation of a directly Ir-B bonded system described by limiting boryl (Ir-B) and borylene (Ir=B) forms.